Teaching the Turkish language to foreigners at higher education level in Northern Cyprus: An evaluation based on self-perceived dominant intelligence types, twenty-first-century skills and learning technologies - Karakaş Kurt, Esra; Güneyli, Ahmet (Frontiers in Psychology, 2023)
Introduction There are many foreign students in higher education in Northern Cyprus. Both the academic and life skills of these students depend on attaching the necessary importance to their Turkish language teaching. The goal of this study is to examine how university students employ learning technology, twenty-first-century abilities, and perceived categories of intelligence in the process of learning a foreign language. Methods In line with the quantitative research design, this study utilized a descriptive approach. Purposeful and convenience sampling methods were used to create the study sample. As a result, the institution in Northern Cyprus with the largest international student body was chosen. At this university, one of the authors of this study has been employed, and Turkish is the language of teaching. The study sample consisted of 431 university students who took Turkish as a foreign language in the 2021–2022 academic year at the selected university. Results The results of the study revealed a weak yet statistically significant correlation between twenty-first-century skills and usage of foreign language-learning technologies. Additionally, students' twenty-first-century skill scores differed significantly, whereas their foreign language-learning technology scale scores did not match their self-perceived intelligence types. Conclusion The research's findings indicate that students in higher education possess twenty-first-century skills. Based on this finding, it is possible to engage students in the courses and accomplish effective foreign language acquisition if foreign language education is carried out in accordance with modern methodologies and based on twenty-first-century abilities. It has been revealed in this study that it is important to include social learning rather than individual and competitive learning in foreign language education classes.